2019
DOI: 10.1038/s41467-019-13561-z
|View full text |Cite
|
Sign up to set email alerts
|

Atlas of quantitative single-base-resolution N6-methyl-adenine methylomes

Abstract: Various methyltransferases and demethylases catalyse methylation and demethylation of N6-methyladenosine (m6A) and N6,2′-O-dimethyladenosine (m6Am) but precise methylomes uniquely mediated by each methyltransferase/demethylase are still lacking. Here, we develop m6A-Crosslinking-Exonuclease-sequencing (m6ACE-seq) to map transcriptome-wide m6A and m6Am at quantitative single-base-resolution. This allows for the generation of a comprehensive atlas of distinct methylomes uniquely mediated by every individual know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
248
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 158 publications
(258 citation statements)
references
References 55 publications
7
248
0
3
Order By: Relevance
“…We note that the HPLC-MS/MS m6Am signal was derived internally from U2 snRNA as we did not use any decapping enzyme in digesting U2 snRNA, which would prevent the quantification of any cap-adjacent RNA nucleotide. Furthermore, previous and current RNA methylomes have demonstrated that U2 snRNA lacks a TSS-associated adenosine N 6 -methylation ( Figure 1C) (27). Altogether, this demonstrates that METTL4 is necessary for m6Am formation within U2 snRNA.…”
Section: U2 Snrna M6am Is Absent In Mettl4-ko Cellssupporting
confidence: 68%
See 4 more Smart Citations
“…We note that the HPLC-MS/MS m6Am signal was derived internally from U2 snRNA as we did not use any decapping enzyme in digesting U2 snRNA, which would prevent the quantification of any cap-adjacent RNA nucleotide. Furthermore, previous and current RNA methylomes have demonstrated that U2 snRNA lacks a TSS-associated adenosine N 6 -methylation ( Figure 1C) (27). Altogether, this demonstrates that METTL4 is necessary for m6Am formation within U2 snRNA.…”
Section: U2 Snrna M6am Is Absent In Mettl4-ko Cellssupporting
confidence: 68%
“…By overexpressing recombinant METTL4, we demonstrated the necessity of METTL4's catalytic site in its methylation activity and that METTL4 is able to directly methylate U2 snRNA both in vitro and in vivo. N 6 -methylation writers such as METTL3 and PCIF1 have multiple in vivo targets and thus by comparing the difference in precise RNA methylomes before and after depleting these writers in cells, we can determine the in vivo target RNA preference for each writer (27). METTL4 however, only has 1 clear in vivo target, making such an analysis non-trivial.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations